Self-reported needs of people living with psychotic disorders: Results from the Australian national psychosis survey - Migliorini, Christine; Fossey, Ellie; Harvey, Carol (Frontiers in Psychiatry, 2022)
Person-centered care is a collaborative approach to health care. To provide effective, person-centered care to people living with severe mental illness, it is necessary to understand how people view their own needs. The Perceived Need for Care Questionnaire (PNCQ) was used in the Australian National Survey of High Impact Psychosis (SHIP) to deepen understanding and evaluate, at a population level, the needs of Australian adults living with psychotic illness. SHIP participants were 1,825 adults, aged 18–65 years, living with psychotic illness and in contact with public specialized mental health services across Australia in 2010. The survey package included demographic and clinical items, and various scales including the PNCQ appraising a comprehensive range of life domains. Logistic regressions measured the impact that various demographic, clinical and psychosocial independent variables (e.g., loneliness, health-related quality of life, disability, accommodation type) had on the likelihood of inadequately met PNCQ domain-related need. Over two-thirds of people living with psychosis reported at least two areas of unmet need for care despite most being in contact with mental health services. Work or using one's time and socializing, counseling, and self-care domains had the largest proportion of inadequately met needs (range between 49 and 57%). Feelings of loneliness and/or social isolation were significantly associated with unmet needs across all PNCQ domains, except for financial needs. Health-related quality of life was significantly associated with unmet needs across all domains, except for housing needs. Disability was significantly associated with unmet social, occupation (work or time use), housing and medication-related needs. Consumers view their needs for care as unmet across many life areas despite being in contact with mental health services. Loneliness, unmet psychosocial needs, and health-related quality of life appear strongly interconnected and warrant greater attention in the delivery of person-centered care for people living with psychosis. Support to address social, work or time use and housing related needs among people living with psychosis appears less well targeted toward those with disability. Results underscore the link between quality of life, recovery and needs. These inter-relationships should be considered in mental health services research and evaluation.